Abdülcelîl b. Mollâ Cemîl ve Nasîhatü’l-Mülûk Tercümesi Üzerine - Biner, Fuat (FSM Vakıf Üniversitesi, 2016)
İmam-ı Gazâlî (öl. 1111) tarafından Farsça olarak te’lîf edilen Nasîhatü’l-Mülûk adlı eser birçok farklı dile tercüme edilmiştir. Hem siyâsetnâme hem de nasîhâtnâme türüne giren eser, dünya ve ahiret saadetine ulaştıracak temel ilke ve prensiplerle dönemin hükümdar ve padişahlarına tavsiyelerde bulunur. Gazâlî bu eserinde bir taraftan ideâl bir (devlet adamı, idareci) portresi resmederken, bir taraftan bu modeli devletin idarecisinden, ta kapıkuluna dek her bireyine örnek teşkil edecek biçimde derli toplu bir halde anlatmıştır. Bu çalışmada, Nasîhatü’l-Mülûk adlı eserin Abdülcelîl b. Mollâ Cemîl (ö. 1734’ten sonra) tarafından Türkçeye yapılan tercümesi tanıtılmış, sonra tercümenin muhtevası hakkında bilgiler verilmiştir. Ayrıca eserin tercüme yöntemi hakkında kısa izahlar yapılmıştır.

Nasihatü’l Mülûk, which was written in Persian by Imam al-Ghazzali (d. 1111) has been translated in many languages. This book can be considered as both political treatise and advisor.This book advice to emperors and sovereigns advice basic principles and elements to be happy in both life and afterlife. Gazali creates ideal emperor model on the other hand he defines this model to persons who lord, soldier or even a normal person. He gives a role model to these persons. In this study, the translation of Nasihatü’l Mülûk which is translated by Abdülcelîl b. Mollâ Cemîl (d. after 1734) is presented and then the information of content is given. Also the technique used for translation is briefly inrroduced.
This Article is About Abdülcelil b. Molla Cemil Nasihat Mülük’s Translation
Keywords: Nasîhat-mülûk; Gazâlî; Siyâsetnâme; Nasîhatnâme; Tercüme ve tercüme usûlü; Ghazzali; Nasihatü’l-mülûk; Translation and translation methods